Role of oxygen free radicals in the proliferation of myofibroblasts induced by AngII - Liying Wang; Hong Li; Shijie Yang (Elsevier, 2013)
Previous studies have demonstrated the important role of angiotension II (AngII) in promoting proliferation of myofibroblasts (myoFbs) and myocardial fibrosis. However, the underlying mechanisms and the role of oxygen free radicals in the proliferation of myofibroblasts induced by AngII are unclear. The present study was designed to shed light on this issue through exploration of AngII signaling pathways via in vitro experiments. Primary cultures of neonatal rat myoFbs were divided into five groups which were treated with AngII (10−8 to 10−6 M), AngII with the antioxidant N-acetyl-L-cysteine (NAC), or normal culture medium. We observed the proliferation of myoFbs as induced by AngII at different concentrations with MTT. Reactive oxygen species (ROS) levels in myoFbs were detected by monitoring the fluorescence of 2',7'-dichlorofluorescein. The contents and levels of oxygen free radicals (OH·) in the three groups were detected by spectrophotometer, immunocytochemical staining, and confocal fluorescence. Western blot and image analysis were used to measure membrane translocation and expression of phospho-protein kinase Cα. MyoFbs incubated with AngII (10−8 to 10−6 M) for 24 h increased their rate of proliferation, the content of OH·, and expression of ROS (P<0.01 vs. control group), whereas these parameters decreased in the presence of NAC. Immunocytochemistry, confocal fluorescence staining and image analysis showed that AngII could promote the translocation and expression of p-PKCα in membrane, and the antioxidant NAC blocked this increase (P<0.01). Western blot results also showed that NAC could inhibit the expression of p-PKCα.